2012
DOI: 10.1007/s11894-012-0278-0
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic Gastrointestinal Consequences Associated With Campylobacter

Abstract: Campylobacteriosis is a leading cause of acute infectious diarrhea in the developing world, where it causes considerable mortality, and in developed countries, where it accounts for significant healthcare and other costs. Evidence has emerged from basic science, clinical, and epidemiological domains that suggests that Campylobacter infection is not limited to acute illness but is also involved in the development of well-described extraintestinal sequelae, such as the Guillain-Barré syndrome and reactive arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 90 publications
0
44
1
1
Order By: Relevance
“…Celiac disease is estimated to affect approximately 1% of people worldwide (173,174), and the incidence of this disease has increased up to 5-fold in some countries, including the United States (175). In 2007, a case study described for the first time the development of celiac disease in a young healthy woman following infection with C. jejuni (176).…”
Section: Celiac Diseasementioning
confidence: 99%
“…Celiac disease is estimated to affect approximately 1% of people worldwide (173,174), and the incidence of this disease has increased up to 5-fold in some countries, including the United States (175). In 2007, a case study described for the first time the development of celiac disease in a young healthy woman following infection with C. jejuni (176).…”
Section: Celiac Diseasementioning
confidence: 99%
“…Although complications are rare, they may include cholecystitis (gallbladder infection), pancreatitis and gastrointestinal hemorrhage (Allo, 2001). Immunoreactive complications include reactive arthritis and Guillain-Barré syndrome, a demyelinating autoimmune disorder leading to nerve damage and sometimes death (Riddle, 2012).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…with human infections and several epidemiological studies showed that food, particularly contaminated poultry meat and chicken meat food products, are mainly connected with a risk of human campylobacteriosis (Adkin et al 2006, Nauta et al 2007, Riddle et al 2012. Poultry are asymptomatic carriers of Campylobacter and the infected flocks cannot be identified by clinical symptoms in birds (Berry et al 1988, Newell et al 2001, Newell and Fearnley 2003, Wieczorek and Osek 2005, Adkin et al 2006, Bull et al 2006, Allen et al 2007, Wirz et al 2010, Hue et al 2011, Ridley et al 2011, Habib et al 2012.…”
mentioning
confidence: 99%